Deep Gaussian Mixture-Hidden Markov Model for Classification of EEG Signals - Wang, Min; Abdelfattah, Sherif; Moustafa, Nour; Hu, Jiankun (IEEE transactions on emerging topics in computational intelligence, 2018)
Electroencephalography (EEG) signals are complex dynamic phenomena that exhibit nonlinear and nonstationary behaviors. These characteristics tend to undermine the reliability of existing hand-crafted EEG features that ignore time-varying information and impair the performances of classification models. In this paper, we propose a novel method that can automatically capture the nonstationary dynamics of EEG signals for diverse classification tasks. It consists of two components. The first component uses an autoregressive-deep variational autoencoder model for automatic feature extraction, and the second component uses a Gaussian mixture-hidden Markov model for EEG classification with the extracted features. We compare the performance of our proposed method and the state-of-the-art methods in two EEG classification tasks, subject, and event classification. Results show that our approach outperforms the others by averages of \text{15}%± \text{6.3} (p-value <\text{0.05} ) and \text{22}%± \text{5.7} (p-value <\text{0.05} ) for subject and event classifications, respectively.